Efektivitas Media Video dan Leaflet dalam Edukasi DAGUSIBU (Dapatkan, Gunakan, Simpan, Buang) dan Beyond Use Date: Studi Kuasi-Eksperimen - Hasanah , Fenny; Lubis, Salmah Handayani; Dasopang , Eva Sartika; Aisyah, Teti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: The increasing practice of self-medication and home drug storage carries the potential for medication management errors, including improper drug disposal. Lack of public understanding of DAGUSIBU (Acquire, Use, Store, Dispose) protocols and Beyond Use Date (BUD) may lead to drug misuse and environmental contamination due to improper disposal methods that violate the Drug Awareness Family Movement (Gerakan Keluarga Sadar Obat/GKSO) guidelines. Objective: To examine the impact of educational interventions on public knowledge of DAGUSIBU and BUD, and to compare the effectiveness of video versus leaflet media. Methods: A quasi-experimental study with pretest-posttest design was conducted. Purposive sampling was used to select 100 respondents from Kotamatsum I Subdistrict. Data were analyzed using Wilcoxon test (educational impact), Chi-Square test (demographic correlations), and Mann-Whitney test (media comparison). Results: The educational intervention significantly improved participants' knowledge of DAGUSIBU and BUD (p < 0.001). Gender significantly influenced knowledge improvement (p = 0.005), while age, education level, and occupation showed no significant effects. Video proved more effective for DAGUSIBU content (mean score 53.94 vs 47.06), whereas leaflets showed marginally better results for BUD material (50.56 vs 50.44).Conclusion: Both video and leaflet-based education effectively enhanced community knowledge. Videos are recommended for DAGUSIBU campaigns, while leaflets serve as suitable supplementary materials for BUD education.